Playdough Media to Increase Creativity in Early Childhood - Muryani, Sri; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
21st-century skills, which are the main things that children must master, prioritize the 4C, namely creativity, critical thinking, communication, and collaboration, where the learning process will prioritize skills that adapt to the conditions of the time. Creativity in early childhood is also characterized by the ability to form imagination. To foster creativity, children need to play, one of which is playing playdough. This research aims to analyse playdough media to increase creativity in early childhood. The research method used is descriptive. Data was obtained from interviews, observations, and documentation sources from TK Aisyiyah 14 Danukusuman. The collected data was analysed based on the Miles & Huberman model, namely data reduction, data display, and conclusion. Based on research and interviews with heads, and teachers, it can be concluded that playdough can stimulate children’s creativity because playdough is a safe medium, easy to find material, easy to shape, and children independent, and confident. Self-confidence, courage to express opinions, and high curiosity are characteristics of creative children.